Factors Associated With Recurrent Urinary Tract Infections Among Females Of Reproductive Age At Kisugu Health Centre III, Uganda - Kavuma Sharif (My University, 2022)
Women of reproductive age in Uganda still suffer from recurrent urinary tract infections (UTIs), a major public health problem. The assessment of factors associated with recurrent UTIs among females aged 15 – 49 years attending Kisugu Health Centre III, Kampala. A cross-sectional study conducted on 144 randomly selected samples with the help of an interviewer-administered questionnaire to assess knowledge, attitudes and practices of recurrent UTI. The analysis of data was done in SPSS version 21. For the association, chi-square was applied at p<0.05. Of participants 36.8% had recurrent UTIs. Most of the respondents admitted that UTIs can recur, but only 53.5% showed good overall knowledge which was significantly associated with recurrence (p=0.049). The improper technique of wiping, high level of coitus, poor medication adherence and co-existing disease conditions like diabetes. Although individuals generally opted to seek health care, difficulty in getting the support they needed was a barrier they faced due to embarrassment. According to this study, strengthening preventive measures and providing enhanced counselling and targeted health education will help reduce recurrent UTIs in females.
Keywords: Recurrent urinary tract infections; Women of reproductive age; Knowledge attitudes; practices; Associated factors; Kisugu Health Centre III; Uganda; Public health